Paraspinal Muscle Stiffness during Hamstring Exercise Using Shear-Wave Elastography - Eleftherios Kellis; Afxentios Kekelekis; Eleni E. Drakonaki (MDPI AG, 2024)
Soccer teams integrate specific exercises into their typical workout programs for injury prevention. This study examined the effects of hamstring exercise on paraspinal and hamstring stiffness. These findings can inform training and rehabilitation programs to improve muscle health and prevent injuries. Fifteen young, healthy males performed passive and active (submaximal) knee flexion efforts from 0°, 45°, to 90° angle of knee flexion from the prone position. Using shear-wave elastography (SWE) and surface electromyography, we measured the elastic modulus and root mean square (RMS) signal of the erector spinae (ES), multifidus (MF), semitendinosus (ST), and semimembranosus (SM) during different knee flexion angles. Passive SWE modulus at 0° was 12.44 ± 4.45 kPa (ES), 13.35 ± 6.12 kPa (MF), 22.01 ± 4.68 kPa (ST), and 21.57 ± 5.22 kPa (SM) and it was greater (p < 0.05) compared to 45° and 90°. The corresponding values during knee flexion contractions at 0° increased to 18.99 ± 6.11 kPa (ES), 20.65 ± 11.31 kPa (MF), 71.21 ± 13.88 kPa (ST), and 70.20 ± 14.29 kPa (SM) and did not differ between angles (p > 0.05). Compared to rest, the relative increase in the SWE modulus during active contraction had a median value (interquartile range) ranging from 68.11 (86.29) to 101.69 (54.33)% for the paraspinal muscles and it was moderately to strongly correlated (r > 0.672) with the corresponding increase of the hamstring muscles [ranging from 225.94 (114.72) to 463.16 (185.16)%]. The RMS signal was greater during active compared to passive conditions, and it was lower at 90° compared to 45° (for SM/ST) and 0° (for all muscles). The association between paraspinal and hamstring passive muscle stiffness indicates a potential transmission of forces through myofascial connections between the lumbar spine and the lower limbs. In this laboratory setting, hamstring exercises affected the stiffness of the paraspinal muscles.